Formações imaginárias e posições-sujeito no discurso acerca do grupo Caipira em Sergipe no século XIX (1885-1890) - Santana, Glêyse Santos (2023)
The Parish of São Paulo da Mata, which was located in the countryside of the Province of Sergipe, was the epicenter of the socio-religious movement, the Caipiras, as they were called in periodicals and ecclesiastical documents in the mid-19th century. During the five years of the movement's existence, the group consisting mostly of rural workers, housewives and artists (artisans), but which also included, in its ranks, some literate men and even some political leaders of the region, was led by the parish priest Felismino Fontes (1848-1919).Considering the time and the territorial space, the number of adherents was numerically representative, since it is estimated, quantitatively, an approximate total of more than two thousand members among the residents of towns, parishes and villages in the region of the current municipalities of Frei Paulo, Lagarto, Carira, Alagadiço, Itabaiana, Simão Dias, going to the limits of the Bahian territory, that is, in the vicinity of Serra Negra. As a result of their beliefs, practices and the unconditional support given to Father Felismino, the Caipiras suffered sanctions such as arrests, beatings and persecution by the state and the leaders of the region. As for the leader, after the suspension of his order, he was exiled and interned in the São João de Deus Asylum, in 1891, by order of the Archbishop of the Metropolitan Curia of Bahia. Given the above, the thesis developed in the field of Language Sciences, more specifically under the theoreticalmethodological framework of materialist Discourse Analysis (AD), had the imaginary formations and subject-positions present in the discourse produced about the Caipiras, in the period temporal from 1890 to 1903, as an object of study. Therefore, through different significant materialities, that is, through the epistles produced by the Caipira leader, the news described in periodicals and the religious documents obtained, the corpus of the present research was selected with the purpose of answering the following questions: Who were the Caipiras? What can the analysis of the Felisminian epistles reveal about the “theological” framework of the group? What are the subject-positions assumed by the speakers in relation to the movement? What are the imaginary formations that subjects build of themselves, their followers and their opponents? And, on the other hand, how were the Caipiras represented by their opponents in ecclesiastical documents and periodicals of the time? What aspects of the Brazilian sociohistorical-ideological formation can be directly related to the fight against the Caipira group? To answer these questions, an analytical device was constructed based on the descriptiveinterpretative beat methodology of AD, which consists of discursive sequences from the different domains to be analyzed, or even, SDE (epistolary discursive sequence), SDC (discourse sequence catholic) and SDP (sequences of periodicals) as they were called. In the next step, the interpretation of discursive materiality was carried out through the mobilization of categories from the discursive theory of AD and from historical and sociological studies. Finally, it was concluded that the different discursive formations and the subject-positions linked to the Caipiras are directly related to the idealization of an autonomous Catholicism with the purpose of promoting the reinterpretation of liturgical and prophetic doctrines, of the debates in the Brazilian religious field and of the political struggles that marked Sergipe's agreste and sertão at the end of the 19th century.